FOSTERING WORK READINESS THROUGH PROFESSIONAL PUBLIC SERVICE VALUES AT SMK RYO YUWARAJA - Muhammad Mughni Labib; Millatus Sholihah; Muhammad Muqoffa (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2026)
The work readiness of Vocational High School (SMK) students is determined not only by the mastery of technical skills but also by an understanding of the professionalism values required in the professional world. One of the competencies that needs to be developed is an understanding of professional public service, which encompasses service ethics, communication, responsibility, and an orientation toward user satisfaction. This community service activity aims to enhance the understanding and work readiness of students at SMK Ryo Yuwaraja through the provision of professional public service values. The implementation method was conducted in four stages: preparation, execution, evaluation, as well as reporting and follow-up. The training sessions were delivered utilizing interactive lectures, discussions, case studies, and public service simulations that engaged active student participation. The results of the activity indicated an increase in students' understanding of professional public service concepts. Students no longer perceived public service merely as an administrative activity, but rather as a process that demands professional attitudes, ethics, effective communication, and accountability in service delivery. Public service simulations proved to be the most effective method in helping students internalize the values of workplace professionalism. In addition to enhancing knowledge, this activity also fostered the development of discipline, responsiveness, and a service-oriented mindset. Consequently, the provision of professional public service values is proven to contribute positively to enhancing the work readiness of vocational school students and strengthening the synergy between higher education institutions and vocational education facilities.